Dampak Motivasi Dan Gaya Kepemimpinan Terhadap Kinerja Pegawai Yayasan Kenanga Gemilang Semarang - Sutaat Sutaat (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This research aims to determine the influence of motivation and leadership style together on performance and to determine the influence of motivation and leadership style partially on the performance of employees of the Kenanga Gemilang Foundation, Semarang. A leader in leading an organization should use existing human resources to achieve goals set by the organization. Employees are resources that can be utilized to achieve organizational goals as fully as possible, and this is very important for a leader to practice a leadership style that suits the organization. The results show that work motivation and leadership style have a positive and significant influence on employee performance. The magnitude of F 282,919 (R2) is 0.953, with a coefficient of determination value of 0.953; thus, it can be interpreted that the magnitude of the influence of the two variables, motivation and leadership style, on performance is 95.3%, while the remaining 4.7% is influenced by other variables.